2018
DOI: 10.1128/jvi.00850-18
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Evolutionary Origin and Positive Selection of the Retroviral Restriction FactorFv1in Muroid Rodents

Abstract: The laboratory mouse gene encodes a retroviral restriction factor that mediates resistance to murine leukemia viruses (MLVs). Sequence similarity between and the protein of the murine endogenous retrovirus-L (MuERV-L) family of ERVs suggests that was co-opted from an ancient provirus. Previous evolutionary studies found orthologs only in the genus. Here, we describe identification of orthologous sequences in several species belonging to multiple families of rodents outside of the genus We show that these ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Similarly, we and others have uncovered equivalent forces acting upon Fv1, (17,(31)(32)(33)) revealing a need for continuous or frequently reoccurring waves of retroviral infection in its maintenance over a ~45 my lifetime (33).…”
Section: Introductionmentioning
confidence: 67%
“…Similarly, we and others have uncovered equivalent forces acting upon Fv1, (17,(31)(32)(33)) revealing a need for continuous or frequently reoccurring waves of retroviral infection in its maintenance over a ~45 my lifetime (33).…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, a captured env gene was found to be conserved in spiny-rayed fishes (Acanthomorpha) for more than 110 million years (40). However, unlike retroviral env genes, few co-opted retroviral gag genes have been identified to date (22,24,25). In this study, we identified two new co-opted retroviral gag genes in mammals, that is, the wcs1 and wcs2 genes, which arose convergently in two major linages of mammals.…”
Section: Discussionmentioning
confidence: 86%
“…5). Both wcs genes are much older than the Fv1 gene, which integrated into the genomes of Muroidea ϳ45 MYA (24,25). The convergent co-option during the early evolution of mammals suggests that co-option of retroviral gag genes might occur more frequently than previously thought.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As part of this ongoing arms-race, while viruses have relied on acquisition and fusion of diverse genes (1), the host-defense mechanism has been made possible by the functional divergence of gene copies following duplication of genes as well as whole-genomes (27). Restriction factors being at the forefront of this long-term conflict (810), show clear molecular signatures of arms-race (11,12). In fact, the presence of these signatures has been proposed to be a hallmark of restriction factors (8,13), and has been used as a screening strategy to identify potential candidates(2,14).…”
Section: Introductionmentioning
confidence: 99%